DESAIN SISTEM BACK-END PADA WEBSITE PROPERTI - Dahlan Susilo; Pranowo Setiaji (Politeknik Bisnis Indonesia, 2023)
The Clee Ltd prioritizes comfort, speed and customer satisfaction and has a high commitment and professionalism in providing services at relatively affordable prices. The website can reach a wider range of customers and make it easier for customers to find information about products and choose the best offers provided by the company, as well as being a promotion. Business websites require good back-end system support to help create a website as a behind-the-scenes system that processes databases and servers. Design a property website system that has 2 users, namely User and Admin. User as website visitor and Admin as website manager. Users can only access 2 pages, namely the